WACC and investment opportunities - Pacheco Mexzon, Raimundo Renaun (2014)
Whereas large investment projects are financed company with a percentage share capital and other resources third way (Debt), analyzing concerns in the period 1999 to 2010 arose whether if Peruvian company listed on Lima The Stock Exchange improved investment opportunities. For this, the behavior of the weighted average cost of capital (WACC) was determined.